2020
DOI: 10.3389/fpsyg.2019.02964
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit of Mental Skills Training on Performance and Stress Response in Military Personnel

Abstract: Mental skills training (MST) has been suggested to reduce stress in civilian and athletic populations, however, whether these techniques and practices transfer to a military population are unknown. Therefore, the purpose of this study was to evaluate two MST programs against a baseline condition, training-as-usual (TAU), during an intense, active-duty, military training environment. Two hundred and three Marines enrolled in the United States Marine Corps' Basic Reconnaissance Course participated in this effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 53 publications
1
15
0
1
Order By: Relevance
“…In line with this theory, previous studies have shown that adaptation to psychological distress occurs during basic training period [47,48]. Although psychological metrics did not show prediction of drop out, in general, enhancing mental skills have shown to be beneficial for soldiers in order to improve cognition and stress control during stressful environment, such as the field training [49].…”
Section: Discussionmentioning
confidence: 86%
“…In line with this theory, previous studies have shown that adaptation to psychological distress occurs during basic training period [47,48]. Although psychological metrics did not show prediction of drop out, in general, enhancing mental skills have shown to be beneficial for soldiers in order to improve cognition and stress control during stressful environment, such as the field training [49].…”
Section: Discussionmentioning
confidence: 86%
“…The most frequently referred outcomes resulting from the interventions were focused in areas of improved skills or increased usage and decreases in burdensome psychosocial aspects (i.e., anxiety or depression). Regarding improvements, some outcomes included higher levels of reported self-confidence (Adler, Bliese, et al, 2015; Adler, Williams et al, 2015; Hammermeister et al, 2009), improved interpersonal communication (Bui et al, 2018; Fischer et al, 2013; Lester et al, 2011; Perlman et al, 2010), greater psychological health (Cohn & Pakenham, 2008; Lester, Liang, et al, 2016; Saltzman et al, 2016), improved performance on physical tasks (Adler, Bliese, et al, 2015; Jensen et al, 2020; Jha et al, 2017), greater resilience and coping skills (Kees & Rosenblum, 2015; Pickering et al, 2010; Sylvia et al, 2020), and enhanced connection with family or transition out of the armed forces environment (DeFraia et al, 2014; Harper et al, 2014). Outcomes involving a decrease in negative psychosocial experiences included decreases in post traumatic stress disorder (PTSD) symptoms (Adler et al, 2009; Blevins et al, 2011; Hilton et al, 2019), lowered depression scores or reduction of depression symptoms (Blevins et al, 2011; Dodge et al, 2018; Kees et al, 2015; Sylvia et al, 2015), and a reduction in anxiety or overall stress (Adler, Williams et al, 2015; Bui et al, 2018; Cohn & Pakenham, 2008; Judkins & Bradley, 2017; Kees & Rosenblum, 2015; Lester et al, 2013; Sylvia et al, 2020; Tenhula et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Mental skills have demonstrated success within athletic populations, performing artists, business professionals, police force officers, and military personnel (Anton et al, 2017). With the demonstrated benefits of mental skills within an armed forces context (Adler, Bliese, et al, 2015; Cohn & Pakenham, 2008; Fitzwater et al, 2018; Jensen et al, 2020; McCaslin et al, 2018; Taylor et al, 2011), it remains to be understood how these skills are applied and what format by which they are implemented.…”
Section: Mental Skills For the Active Membermentioning
confidence: 99%
“…The use of a perceived stress and coping strategies measurement combination is increasingly common in studies of law enforcement officers [3, 23, 24, et al]. It was shown that the use of productive coping strategies is associated with a lower severity of PTSD signs [25], enhancing performance and cognitive function [26] and the development of life skills [27], a decrease in psychological distress [28] and social anxiety [29]. However, this influence is largely determined by factors of the so-called "adaptogenic" context [30], i.e.…”
Section: Introductionmentioning
confidence: 99%